Strain measurements and analyses around the bolt holes of structural steel plate connections using full-field measurements. (15th January 2017) - Toussaint, E.; Durif, S.; Bouchaïr, A.; Grédiac, M.
Graphical abstract: Highlights: Bearing behavior is observed in cover-plate steel connections under tensile tests. Various configurations of hole positions are analyzed with full-field measurements. The grid method is used to measure the strain fields that occur in the specimens. Plastic strain maps are in good agreement with observed failure modes. A FE simulation is performed and results are compared to experimental strain maps. Abstract: The mechanical response of cover-plates connections combines various phenomena such as the contact evolution between bolts and holes, the elastic-plastic behavior of the constitutive materials and the effect of large displacements occurring in some cases. The interaction between the holes in the plates needs to be evaluated regarding various configurations of joint and hole positions, especially to take into account the localization of failure around bolts. The different failure modes such as net section fracture, gross section yielding, shear out and bearing, are difficult to predict because they combine local compression under bolt and shear at loaded end distance of the plate. Numerical models show the complexity of stress distribution around the holes depending on the connection configurations. The main originality of this work is to rely on a full-field measurement technique, namely the grid method, to estimate the strain fields that really occur in the specimens under test. Compared to digital image correlation, this technique features a better compromise between strain resolution and spatial resolution. This enables us to analyze in details the strain distribution on the plates with various configurations for the bolts and holes. Both the elastic and the plastic regimes are analyzed. This approach enables us to understand the evolution of the failure zones regarding the bearing mode. A numerical simulation is finally performed and obtained results are compared with their experimental counterparts. Differences observed highlight the relevance of full-field measurements in the current context of high strain gradients.